Home blood pressure measurements: Advantages and disadvantages compared to office and ambulatory monitoring. (2nd November 2015) - Bonafini, Sara; Fava, Cristiano
Abstract : Home blood pressure monitoring (HBPM) is an easy and standardized tool to measure blood pressure (BP) at home, which is recommended by several national and international guidelines to obtain reliable BP values. It is a useful and dependable measure of BP, which can add information to the more common and standardized methods, such as office (OBPM) and ambulatory blood pressure measurement (ABPM), and sometimes substitute for them. Along with ABPM, HBPM detects out-of-office BP levels, helping to identify the white-coat effect and masked hypertension. Moreover, the large number of BP measurements obtained with HBPM has been demonstrated to be associated with future cardiovascular events and to provide information on day-to-day variability; this is a new aspect, the clinical significance of which is still under evaluation. By giving patients a more active role in the management of their chronic disease, HBPM can improve treatment adherence. The present review focuses on all these aspects and describes the pros and cons of HBPM use compared to OBPM and ABPM. In conclusion, although some aspects need to be clarified, the scientific evidence collected so far should encourage the more widespread use of HBPM in clinical practice.